Prilaku Hidrolis Bendung Karet Diisi Air - Kusuma, Syahril Badri; Abdullah, Dedy Tjahjadi; Saputra, Budi (Department of Civil Engineering, Diponegoro University, 2004)
This paper presents experimental study of hydraulic characteristic of water filled rubber dam. Several parameter had been studied such as v-notch, vibration phenomena, geometry deformation and discharge coefficient. Good agreement was found between experimental study and literature study.The result had shown that: V-notch phenomena does not occur on water filled rubber dam for any deflated height, vibration phenomena was occured when deflated height reach 43% from the actual height, the discharge coefficient for free-flow is bigger than submerged-flo and the deformation were reached for both free flow and submerged flow condition. Keywords: Rubberdam, Experimental Study, Hydraulic CharacteristicPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/2787[How to cite: Kusuma, S.B., Tjahyadi, D., dan Saputra, B., 2004, Prilaku Hidrolis Bendung Karet Diisi Air, Jurnal Media Komunikasi Teknik Sipil, Volume 12, Nomor 3, pp. 100-112]